Battling an African cattle killer: Second-generation vaccine against East Coast fever - Nene, Vishvanath M. (International Livestock Research Institute, 2014)
In this film, Vish Nene director of the Vaccines Biosciences program at ILRI, talks about new research that is seeking to create a second-generation vaccine against East Coast fever.